2021
DOI: 10.1111/faf.12536
|View full text |Cite
|
Sign up to set email alerts
|

Cod movement ecology in a warming world: Circumpolar arctic gadids

Abstract: Understanding fish movement in the Arctic is paramount during the current era of rapidly warming seas, receding sea ice and associated shifting species distributions and fishing effort. We synthesized the literature and identified key knowledge gaps on the movement ecology of Arctic cod (Boreogadus saida) and Polar/Ice cod (Arctogadus glacialis, both Gadidae) in the context of climate change. Standardized web-based English-language literature searches yielded 51 articles directly relevant and 122 indirectly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 187 publications
(521 reference statements)
0
7
0
Order By: Relevance
“…Greenland halibut ( Reinhardtius hippoglossoides ) migration to the offshore is also timed with ice formation ( 58 ), which may suggest that their migration phenology will similarly shift. How Arctic cod ( Boreogadus saida ) in the Eclipse Sound region will respond in the short term to climate shifts is not directly known ( 59 ), but a predicted climate-induced increase in cod biomass could result in higher resource availability in the summer. Prey species community composition is also being modified through northward shifts of temperate zooplankton and fish species, which are often of lower caloric value ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Greenland halibut ( Reinhardtius hippoglossoides ) migration to the offshore is also timed with ice formation ( 58 ), which may suggest that their migration phenology will similarly shift. How Arctic cod ( Boreogadus saida ) in the Eclipse Sound region will respond in the short term to climate shifts is not directly known ( 59 ), but a predicted climate-induced increase in cod biomass could result in higher resource availability in the summer. Prey species community composition is also being modified through northward shifts of temperate zooplankton and fish species, which are often of lower caloric value ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that in 2013 and 2022, data were collected during the "day" (08.45 -17.00 UTC) and "night" (00.10 -04.00 UTC) periods (Table 1), respectively, the second hypothesis proposes an interpretation of the results, taking into account the possible Diel Vertical Migration (DVM) of medium-size fish. Previous studies (Falk-Petersen et al, 2008;Last et al, 2020;Pettitt-Wade et al, 2021) have confirmed that biological clocks of marine organisms are important for shaping their daily activities at high latitudes, and there are some confirmations that organisms could perform DVM in the Arctic during the Polar Night or Polar Day.…”
Section: The Difference In Depth Distributions Of Ts Of Middle-size F...mentioning
confidence: 89%
“…Eastern Beaufort Sea belugas occupied diverse bathymetric habitats during fall, from deep waters of the Arctic Basin to the shallow Chukchi Sea, explaining large variation in dive behavior observed during this period (Figures 4, 8). Benthic diving to >800 m along the Beaufort, Chukchi, and East Siberian slopes (Figure 4) could represent feeding on Greenland halibut, which is found in greatest abundance at seafloor depths ≥500 m (Majewski et al, 2017), when Arctic cod in the Beaufort Sea redistribute into the mesopelagic layer in fall (Geoffroy et al, 2016;Pettitt-Wade et al, 2021). EBS belugas principally made two deep dive types in the Arctic Basin: deeper Deep Pelagic V and shallower Deep Pelagic W dives (Figures 8, 9C), suggesting that two different depth layers were targeted at ∼100-300 m and >500 m (Table 2).…”
Section: Early Fallmentioning
confidence: 99%